2015
DOI: 10.1039/c5cy00058k
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature, solventless telomerization of isoprene with alcohols using (N-heterocyclic carbene)–palladium catalysts

Abstract: The use of a custom-made palladium complex for the telomerisation of isoprene with alcohols under green conditions is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, only monotelomers of glycerol were detected, although the alkylation of some of the PEG could not be suppressed. In 2015, the Pd/NHC‐catalyzed telomerization of isoprene with different alcohols was reported using preformed cationic palladium complexes . High selectivities to head ‐ head ‐products with methanol can remarkably be shifted towards tail ‐ head ‐products if bulkier alcohols are used.…”
Section: 3‐dienesmentioning
confidence: 99%
“…Interestingly, only monotelomers of glycerol were detected, although the alkylation of some of the PEG could not be suppressed. In 2015, the Pd/NHC‐catalyzed telomerization of isoprene with different alcohols was reported using preformed cationic palladium complexes . High selectivities to head ‐ head ‐products with methanol can remarkably be shifted towards tail ‐ head ‐products if bulkier alcohols are used.…”
Section: 3‐dienesmentioning
confidence: 99%
“…An open mechanistic question is whether binding of NEt 3 to the metal center inhibits catalysis by directly competing with alcohol for the binding sites or by promoting formation of off-cycle high-spin alcohol complexes. Binding of NEt 3 to transition metals has been reported in the literature by several research groups. Chaudhuri et al demonstrated that NEt 3 has an inhibitory effect on the aerobic oxidation of alcohols by a Cu complex containing an iminosemiquinone ligand . A similar inhibiting behavior has been observed by Ozerov and Fan for catalytic coupling of acetonitrile with aldehydes by a Ni complex of a diarylamido-based PNP ligand with 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU) as the base .…”
Section: Discussionmentioning
confidence: 99%
“…Oxindole-based hemiterpenes and monoterpenes are a class of biologically active natural products. However, the synthesis of these compounds through prenylation and geranylation of oxindoles encounters substantial hurdles and challenges. First, the four sp 2 carbon atoms in isoprene have similar electronic properties and steric hindrance. As a result, there are six possible addition modes, resulting in a low regioselectivity during the reaction (Scheme a).…”
Section: Introductionmentioning
confidence: 99%